2014
DOI: 10.3846/16486897.2014.926908
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of Heavy Metals in Different Body Tissues of Gibel Carp πΆπ‘Žπ‘Ÿπ‘Žπ‘ π‘ π‘–π‘’π‘  π‘”π‘–π‘π‘’π‘™π‘–π‘œ Separately Exposed to a Model Mixture (Cu, Zn, Ni, Cr, Pb, Cd) and Nickel

Abstract: Heavy metals (HMs) are common persistent pollutants of aquatic ecosystems, which have a property to migrate and accumulate in water organisms. Little information has been compiled on HM accumulation and the interactions between them in fish exposed to their mixtures at environmentally-relevant concentrations. The aim of the present study was to determine accumulation patterns of Cu, Zn, Ni, Cr, Pb and Cd in the muscle, gills and liver of Gibel carp after 14-day exposure to HM model mixture (HMMM) and to Ni sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…In addition, previous studies have pointed out the enrichment of heavy metals in muscle, gills, liver, and kidney of fish (Fazio et al, 2014;Svecevicius et al, 2014;Wei et al, 2014). The NPs enhance the uptake heavy metal and organic toxicants (Baun et al, 2008;Tan et al, 2012;Wang et al, 2012Wang et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have pointed out the enrichment of heavy metals in muscle, gills, liver, and kidney of fish (Fazio et al, 2014;Svecevicius et al, 2014;Wei et al, 2014). The NPs enhance the uptake heavy metal and organic toxicants (Baun et al, 2008;Tan et al, 2012;Wang et al, 2012Wang et al, , 2014.…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained are in full agreement with worldwide research on the zinc content in fish muscle tissue. The symmetry regarding Zn levels in carp muscle tissue from all the mentioned studies is clear evidence that muscle tissue is characterized by low levels of such metals due to their accumulation in organs such as the liver, ovaries, testicles, gills, and kidneys [ 115 , 116 ].…”
Section: Content Of Pb and Zn In The Muscle Tissue Of Common Carp ( ...mentioning
confidence: 99%
“…From this point of view, the muscle tissue is covered on the outside with skin, which prevents direct contact with the environment. According to El-Moselhy et al [ 116 ], another significant reason for the observed asymmetry regarding the concentrations of these elements in muscle tissue and biochemically active organs is that muscle tissue does not play a role in the detoxification process. The lowest level of accumulation in all the organs and tissues is assigned to blood plasma.…”
Section: Content Of Pb and Zn In The Muscle Tissue Of Common Carp ( ...mentioning
confidence: 99%
“…The interactions can be additive, synergistic, or antagonistic. Therefore, the impact of various mixtures of metals in the environment on the survival of fish may vary [ 12 ]. The toxic effects of cadmium manifest in organisms when the metal substitutes other metal ions in essential micro- and macro-elements (mainly Ca 2+ , Zn 2+ , Cu 2+ , and Fe 2+ ) that are part of metalloenzymes, and as a result of its very strong affinity to biological structures containing an –SH group, including proteins, enzymes, and nucleic acids [ 13 ].…”
Section: Introductionmentioning
confidence: 99%